ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN PERPAJAKANNYA (Studi Empiris Pada Pegawai Negeri Sipil Di Lingkup Kecamatan Sumberrejo) - Wahyu Winarno (Fakultas Ekonomi, 2022)
This study aims to determine the effect of Tax Sanctions, Effects of Tax Knowledge, Fiscal Services, and Tax Amnesty to Taxpayer Compliance. The population of this research is the taxpayer of Persons who work as civil servants in Sumberrejo district of Bojonegoro district. Sampling technique using sampling quota which amounted to 38 respondents, with data collection techniques using questionnaires. The collected data was analyzed using SPSS program version 18 with multiple linear regression analysis. The results of this study indicate that: (1) there is no effect of tax levy sanction on taxpayer compliance indicated by the value of t arithmetic of 0.269 and significance value 0.769, (2) there is no influence of tax knowledge variable on taxpayer compliance indicated by niai t arithmetic of 1.054 and significance value of 0.299, (3) there is the effect of tax service variable on taxpayer compliance indicated by the value of t count of 4.205 and the significance value of 0.000, (4) there is no effect of tax amnesty variable on taxpayer compliance is indicated with t value equal to -0.553 and a significance value of 0.584.